Sparky's bark = El ladrido de Sparky - Chapra, Mimi (Katherine Tegen Books, 2006)
When young Lucy travels from Latin America to visit relatives in Ohio, she is very homesick until she realizes that the only way to communicate with her cousin's frisky dog is to learn to speak English.